(untitled) (Revista Apotheke, 2021)
This article aims to correlate the foundations of the philosophical movement of existentialism in the 40s and 50s, with the artistic works of Alberto Giacometti, Eugène Ionesco and Albert Camus. The analysis will be anchored by the sculpture Nose (1947), by Giacometti, by the play Rhinoceros (1959), by Ionesco, and by the book The foreigner (1942), by Camus. All works will be interpreted in the light of existentialism and its counterpoint to the Covid-19 pandemic that has been plaguing the planet since 2020.